Teachers’ Responses to the Challenges and Problems in English Reading Faced by the Students Suspected with Dyslexia. - Asmah Dien Amaliah; Sukardi Weda; Sahril (International Journal of Language, Education, and Literature, 2026)
Reading difficulties experienced by students suspected of having dyslexia remain a critical issue, especially in contexts where English is taught as a foreign language. Although existing studies describe the cognitive and linguistic features of dyslexia, limited attention has been given to how teachers respond to these challenges in real classroom situations, creating a gap between theory and practice. This study aims to address this gap by examining teachers’ responses to the English reading problems encountered by students suspected of dyslexia at SMP Negeri 2 Sinjai. Using a qualitative descriptive design, data were collected through classroom observations, interviews with English teachers, and analysis of relevant documents. The findings reveal that these students struggle with decoding, phonological awareness, fluency, and overall comprehension, often requiring additional time and support to understand reading texts. Teachers employed several strategies, including phonics-based instruction, vocabulary reinforcement, simplified reading materials, and individualized assistance. However, the study also found that many teachers lacked sufficient knowledge about dyslexia and had limited access to specialized training, resulting in inconsistent instructional approaches. In conclusion, the study underscores the need for stronger teacher preparation, more structured literacy interventions, and clear guidelines to better support students suspected of dyslexia in developing their English reading skills